Impact of Hospital Visitor Restrictions on Racial Disparities in Obstetrics (Mary Ann Liebert, 2020)
Racial disparities in both obstetrics and COVID-19 are well documented. Troublingly, implicit biases and related testimonial injustice potentiate adverse outcomes for women of color whose voices and concerns have been historically discredited by the medical establishment. In the context of COVID-19, the restriction of hospital visitors for infection prevention and control in a labor and delivery setting may disproportionately burden black women by eliminating or severely limiting access to essential in-person advocacy, which threatens to exacerbate existing disparities in maternal and neonatal outcomes. The potential disproportionate impact of visitor restrictions on women of color should inform the ongoing pandemic response.